2020
DOI: 10.1108/ijdrbe-01-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

The role of perception of local government officials on climate change and resilient development: a case of Uttarakhand, India

Abstract: Purpose This paper aims to gain insight on the perception and role of the local government officials on climate change and resilience in Uttarakhand, India. Uttarakhand, being a sensitive mountainous region in India, faces the brunt of frequent climate-related disasters and their severe impacts. Therefore, it is crucial to understand how authorities perceive the issue of climate-related disasters and their level of commitment toward mitigation and adaptation programs. Design/methodology/approach The literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Authorities' knowledge sufficiency is very important in disaster preparedness. This is supported by Chondol et al (2020), whom argued that the perceptions, understanding and knowledge of officers play an important role in decisionmaking in disaster mitigation, increasing capacity building and dissemination of awareness on disaster risk reduction. Another supporting factor is that Aceh province is a disasterprone area.…”
Section: Discussionmentioning
confidence: 93%
“…Authorities' knowledge sufficiency is very important in disaster preparedness. This is supported by Chondol et al (2020), whom argued that the perceptions, understanding and knowledge of officers play an important role in decisionmaking in disaster mitigation, increasing capacity building and dissemination of awareness on disaster risk reduction. Another supporting factor is that Aceh province is a disasterprone area.…”
Section: Discussionmentioning
confidence: 93%
“…Public officials in this study outlined the limited financial resources and issues with political leadership as challenges that need to be addressed to build adaptive resilience. Chondol et al [12] also found scarcity of resources as a reason for lack of community level capacity building efforts.…”
Section: Similarities and Differences In Community Resilience Percept...mentioning
confidence: 99%
“…Numerous articles, such as [2,[5][6][7][8], have explored community resilience using a more theoretical literature review approach. Several studies [9][10][11][12][13] have explored community resilience using a survey approach. However, few studies, such as [4,14,15], have examined community resilience using a qualitative interview-based approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is particularly relevant to mountains due to their geographic and socio-economic characteristics (e.g. dissected topography, scattered settlement, lower population density than in lowlands) (Charlery de la Masselière et al, 2017 [48]). Central governments remain in charge of developing relevant strategies and plans (e.g.…”
Section: Institutional Arrangements For Multi-level Policy Co-ordinationmentioning
confidence: 99%